2019
DOI: 10.1111/1365-2435.13327
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of soil chemistry on the foliar resorption of nitrogen and phosphorus across altitudinal gradients

Abstract: Nutrient resorption from senescing leaves prior to litterfall is a strategy for nutrient conservation in vascular plants. However, the mechanisms through which soil fertility and/or foliar nutrient status affect nutrient resorption are not yet fully known. We used two 1,000‐m‐wide altitudinal gradients on two different bedrock types (carbonate and silicate) for analysing the interactive effects of temperature and soil chemistry on the resorption efficiency of two major nutrients, nitrogen (N) and phosphorus (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 47 publications
1
18
1
Order By: Relevance
“…Thus, warming potentially delays foliar senescence (Chung et al, 2013) and consequently increases foliar plant P resorption (Estiarte & Peñuelas, 2015). Moreover, it is noted that plant P resorption increased with P supply derived from soil (i.e.,enhanced P mineralization and dissolution) under warming, which contradicts the view on a trade-off between nutrient resorption and soil nutrient supply (Vergutz et al, 2012;Gerdol et al, 2019). We found that increased P resorption was likely driven by warming-induced drying soil (Fig.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Thus, warming potentially delays foliar senescence (Chung et al, 2013) and consequently increases foliar plant P resorption (Estiarte & Peñuelas, 2015). Moreover, it is noted that plant P resorption increased with P supply derived from soil (i.e.,enhanced P mineralization and dissolution) under warming, which contradicts the view on a trade-off between nutrient resorption and soil nutrient supply (Vergutz et al, 2012;Gerdol et al, 2019). We found that increased P resorption was likely driven by warming-induced drying soil (Fig.…”
Section: Discussioncontrasting
confidence: 71%
“…However, these studies ignore a important P supply process: plant P resorption that is a crucial strategy for plants to improve P use efficiency and reduce the dependence of plant growth on soil P availability (Vitousek et al, 1982;Yuan & Chen, 2009). In resorption theory, the magnitude of plant P resorption is considered to be a trade-off with P derived from soil, especially from P mineralization (Vergutz et al, 2012;Gerdol et al, 2019). For instance, plants might retain adequate P concentrations in foliar tissues through increased plant P resorption when soil P availability is insufficient under warming (Yuan & Chen, 2015;Zong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies showed that total soil P need not represent an index of P availability where most of the total soil P consists of recalcitrant organic or inorganic P forms (Gerdol et al, 2017). We speculate that soils richer in fine particle with higher C content enhanced microbial P mineralisation that is the main source of inorganic P supply to the plants in alpine soils (Gerdol et al, 2019). Whatever the mechanism accounting for soil P availability, adequate levels of P supply were important for preventing stoichiometric imbalance between N and P content in the leaves and consequent lowering of the growth rates (Gerdol et al, 2017).…”
Section: Production and Foliar Traitsmentioning
confidence: 73%
“…Nutrient resorption efficiencies increased with increasing mature leaf nutrient concentrations across species and climate treatments and also when only considering plants growing in control plots (i.e., subjected to ambient temperatures, p < .05). This evidence points to a positive influence of plant nutrient status on nutrient resorption efficiency in infertile habitats (Aerts, ; Diehl et al, ; Du et al, ; Gerdol et al, ; Sun et al, ). Senesced leaf N concentrations were well below the complete resorption limit in all treatments (<7 mg/g N in senesced leaves, Killingbeck, ) so the lower mature leaf N concentrations in plants growing under warming (W and W+RR) conditions was likely the reason for the lower N resorption.…”
Section: Discussionmentioning
confidence: 96%
“…The lower nutrient resorption efficiencies observed under warming conditions could be the result of (a) lower initial leaf nutrient contents in mature leaves from warmed plots, (b) a lower plant demand of resorbed nutrients in response to a reduced investment in reproduction (Tully, Wood, & Schwantes, 2013), or (c) impaired physiological mechanisms involved in nutrient resorption processes with warming (Suseela et al, 2015). Soil nutrient availability modulates plant nutrient conservation strategies so that plants in poorer environments tend to have greater resorption efficiencies (Gerdol, Iacumin, & Brancaleoni, 2019;Killingbeck, 1996;Oleksyn et al, 2003). Global studies conducted across a wide range of plant functional types reported negative relationships between leaf nutrient status and resorption efficiencies (Kobe, Lepczyk, & Iyer, 2005;Vergutz et al, 2012), which was attributed to a greater need of recycling leaf nutrients in nutrient-poor leaves.…”
Section: Warming and Rainfall Reduction Effects On Nutrient Resorptmentioning
confidence: 99%